The Influence of the Flame Stabilization Air Intake Holes Diameter on the no Production in an Industrial Gas Turbine. (2015) - Crismaru, Ionut Vasile; Dragomir-Stanciu, Daniel
Abstract: Combustion chambers have a very important role in the functioning and efficiency of gas turbine engines. The role of a combustion chamber is to convert the chemical energy of a fuel, in the presence of air, into thermal energy so that the working fluid of the engine can be expanded inside a turbine. By doing so, the turbine produces mechanical work at the shaft which can be again converted in electrical energy by an electric generator if the gas turbine engine is for industrial use. One important aspect regarding the combustion processes that take place inside the combustion chamber is the quantity of NOx it produces. This paper analyses the influence of the flame stabilization air intake holes diameter on the quantity of NO present in the exhaust flue gas and also the exhaust flue gas temperature which will greatly influence the gas turbine efficiency.